Evaluation of the association between serum uric acid level and the predicted risk score of sudden cardiac death in five years in patients with hypertrophic cardiomyopathy - Sinem Özyılmaz; Muhammet Hulusi Satılmışoğlu; Mehmet Gül; Huseyin Uyarel; Osman Akin Serdar (KARE Publishing, 2018)
Objective: The aim of this study was to determine the relationship between serum uric acid (UA) level and the predicted risk score for sudden cardiac death in 5 years (the HCM Risk-SCD), galectin-3 level, and positive fragmented QRS (fQRS) on electrocardiography (ECG) in patients with hypertrophic cardiomyopathy (HCM). Methods: This was a prospective, observational study. In all, 115 consecutive patients (age >17 years) with HCM and 80 healthy participants were included in the study. The HCM Risk-SCD score (%), galectin-3 level, and fQRS on ECG were evaluated in all patients. Results: The serum UA, galectin-3 level, UA/Creatinine ratio, incidence of ventricular tachycardia (VT) and syncope, and some echocardiographic parameters were significantly higher in the patient group than in the control group (all p<0.05). The UA value was significantly higher in patients with a high score on the HCM Risk-SCD, a positive fQRS, a high galectin-3 level, VT incidence, and need for implantable cardioverter defibrillator (ICD) implantation or cardiopulmonary resuscitation (CPR) than in those without (HCM Risk-SCD >6%. Namely, HCM Risk-SCD >6%, UA: 6.71+-1.29 mg/dL, HCM Risk-SCD ≤5.9%, UA: 5.84+-1.39 mg/dL, p=0.001; fQRS(+), UA: 6.56+-1.20 mg/dL, fQRS(-), UA: 5.63+-1.49 mg/dL, p<0.001; galectin-3 >6.320 pg/mL, UA: 6.56+-1.27 mg/dL, galectin-3 ≤6.310 pg/mL, p=0.016; left atrium anterior-posterior dimension (LAAPD) >36 mm, UA: 6.31+-1.33 mg/dL, LAAPD <36 mm, UA: 5.20+-1.60 mg/dL, p=0.005; VT(+), UA: 6.83+-1.19 mg/dL, VT(-), UA: 5.97+-1.42 mg/dL, p=0.008; ICD(+), UA: 7.08+-0.88 mg/dL, ICD(-), UA: 6.06+-1.42 mg/dL, p=0.022; CPR(+), UA: 7.03+-0.96 mg/dL, CPR(-), UA: 6.04+-1.42 mg/dL, p=0.018. A statistically significant correlation was observed between UA and HCM Risk-SCD, galectin-3 level, LAAPD, and left ventricular (LV) mass (LVM) (r and p values, respectively: 0.355, <0.001; 0.297, 0.002; 0.309, 0.001; 0.276, 0.003. Conclusion: The serum UA level was significantly higher in patients with HCM compared with the control group. A high UA level was associated with a higher HCM Risk-SCD score, positive fQRS, higher galectin-3 level, greater LAAPD, VT incidence, and the need for ICD implantation and CPR in patients with HCM.